Multiple effects of toxins isolated from Crotalus durissus terrificus on the hepatitis C virus life cycle - Shimizu, Jacqueline Farinha [UNESP]; Pereira, Carina Machado [UNESP]; Bittar, Cintia [UNESP]; Batista, Mariana Nogueira [UNESP]; Fernandes Campos, Guilherme Rodrigues [UNESP]; Silva, Suely da [UNESP]; Oliveira Cintra, Adelia Cristina; Zothner, Carsten; Harris, Mark; Sampaio, Suely Vilela; Aquino, Victor Hugo; Rahal, Paula [UNESP]; et al. (Public Library Science, 2017)
Hepatitis C virus (HCV) is one of the main causes of liver disease and transplantation worldwide. Current therapy is expensive, presents additional side effects and viral resistance has been described. Therefore, studies for developing more efficient antivirals against HCV are needed. Compounds isolated from animal venoms have shown antiviral activity against some viruses such as Dengue virus, Yellow fever virus and Measles virus. In this study, we evaluated the effect of the complex crotoxin (CX) and its subunits crotapotin (CP) and phospholipase A(2) (PLA(2)-CB) isolated from the venom of Crotalus durissus terrificus on HCV life cycle. Huh 7.5 cells were infected with HCVcc JFH-1 strain in the presence or absence of these toxins and virus was titrated by focus formation units assay or by qPCR. Toxins were added to the cells at different time points depending on the stage of virus life cycle to be evaluated. The results showed that treatment with PLA(2)-CB inhibited HCV entry and replication but no effect on HCV release was observed. CX reduced virus entry and release but not replication. By treating cells with CP, an antiviral effect was observed on HCV release, the only stage inhibited by this compound. Our data demonstrated the multiple antiviral effects of toxins from animal venoms on HCV life cycle.